Pig Kidney Xenotransplantation as an Alternative Solution for Hifdz Al Nafs - Qotadah, Hudzaifah Achmad; Syarifah, Maisyatusy (International Journal of Islamic Khazanah, 2022)
Recently, US surgeons successfully tested pig kidney transplants on a human patient, which surprised the medical community. This has elicited a range of responses, including among Muslim communities about whether it is permitted by Shariah or vice versa. Some Muslim scholars have stated that pigs are prohibited animals under Islamic law. In contrast, others saw this success as the most recent alternative treatment for kidney failure in recent history. This research examines the issue of transplanting pig kidneys into human bodies by maqasid al-syari'ah (hifdz al-nafs). The full qualitative method was employed based on library research to investigate the stated problems, and all the findings were analyzed descriptively. The study shows, first and foremost, that a pig is one kind of animal that is prohibited under Islamic law in any form. Two conditions must be fulfilled before the transplant of a pig's kidney into a human body can be justified: (1) it must be performed in an emergency where there is no alternative medicine or other sacred organs available; and (2) the harm resulting from the transplant itself must be less than the harm resulting from not performing the transplant. Thus, the transplantation of a pig's kidney into a human body is part of the hifdz al nafs effort to implement maqasid al dharuriyyat for the patient's survival. This study contributes to contemporary Islamic medical ethics by addressing a critical biomedical innovation rarely explored in classical jurisprudence.